Folk economics and folk ethics as problems of moral reasoning: Ordonomic inspirations for business ethics - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2023)
Folk economics' is the economic 'theory' of common sense, and analogously 'folk ethics' is the moral 'theory' of common sense. Typical of 'folk-economic beliefs' are erroneous causal attributions. Typical of 'folk-ethical beliefs' are utopian or dysfunctional criteria for moral judgments. The main proposition of this article is that these two sources of positive and normative disorientation should be made an object of research in business ethics in order to scientifically work on the hitherto neglected area of unjustified moral critiques of the market economy - in addition and complementation to the important area of justified moral critiques of the market economy. In support of this proposition, practical syllogisms are used to show that the scientific critique and correction of 'folk-economic beliefs' requires a slightly different approach than the scientific critique and correction of 'folk-ethical beliefs'. – – 'Folk Economics' ist die Wirtschafts-'Theorie' und analog ist 'Folk Ethics' die Moral-"Theorie" des gesundes Menschenverstandes. Typisch für 'folk-economic beliefs' sind fehlerhafte Kausalattributionen. Typisch für 'folk-ethical beliefs' sind utopische oder dysfunktionale Bewertungsmaßstäbe. Die Hauptthese dieses Aufsatzes besagt, dass diese beiden Quellen positiver und normativer Desorientierung zu einem Forschungsobjekt der Business Ethics gemacht werden sollten, um - neben dem wichtigen Bereich gerechtfertigter Moralkritik an der Wirtschaft - auch den bislang vernachlässigten Bereich einer ungerechtfertigten Moralkritik an der Marktwirtschaft wissenschaftlich zu bearbeiten. Zur Unterstützung dieser These wird anhand praktischer Syllogismen gezeigt, dass die wissenschaftliche Kritik und Korrektur von 'folk-economic beliefs' eine etwas andere Vorgehensweise erfordert als die wissenschaftliche Kritik und Korrektur von 'folk-ethical beliefs'.
urn:nbn:de:gbv:3:2-995489
Keywords: A12; A13; B41; B52; L51; 330; Business Ethics; Folk-economic Beliefs; Folk-ethical Beliefs; Practical Syllogism; Praktischer Syllogismus